2012
DOI: 10.1074/jbc.m111.304576
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Stress Response Modulates Cellular Redox State via Induction of Cystathionine γ-Lyase

Abstract: Background:The integrated stress response (ISR) maintains cellular homeostasis during aberrant protein folding (ER stress). Results:The ISR enhances glutathione synthesis through up-regulation of cystathionine ␥-lyase via the eIF2␣-ATF4 pathway. Conclusion: Cells undergoing the ISR induce cystathionine ␥-lyase, thereby maintaining cellular homeostasis. Significance: These findings link the cells response to ER stress and redox homeostasis through the ISR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 59 publications
(76 reference statements)
9
80
0
1
Order By: Relevance
“…Nrf2 and ATF4 have been found to increase GSH production via multiple mechanisms (44). However, loss of ATF4 impairs GSH production by inhibiting the expression of CTH (45). However, the relevance between TMZ-induced increase of Nrf2 and ATF4 expression and the CTH enzyme regulation, and whether TMZ induced other related enzymes such as CBS (cystathionine β-synthase) in the trans sulfuration pathway for GSH synthesis remain to be clarified and the experiments confirmed.…”
Section: Discussionmentioning
confidence: 82%
“…Nrf2 and ATF4 have been found to increase GSH production via multiple mechanisms (44). However, loss of ATF4 impairs GSH production by inhibiting the expression of CTH (45). However, the relevance between TMZ-induced increase of Nrf2 and ATF4 expression and the CTH enzyme regulation, and whether TMZ induced other related enzymes such as CBS (cystathionine β-synthase) in the trans sulfuration pathway for GSH synthesis remain to be clarified and the experiments confirmed.…”
Section: Discussionmentioning
confidence: 82%
“…eIF2α signaling has previously been implicated in mediating resistance to oxidative stress (31) by increasing intracellular cysteine and GSH synthesis. Increased cysteine levels are mediated through eIF2α-and ATF4-dependent expression of cystine/glutamate transporter xCT (SLC7A11) (32), a subunit specific to the cystine/glutamate antiporter system Xc − , as well as cystathione γ-lyase (CTH), which produces intracellular cysteine from serine-and homocysteine-derived cystathione (33). We found that, in control cells, xCT and CTH are induced during cyclic hypoxia (Fig.…”
Section: Comparison Of Hif-1 and Eif2α Signaling Pathways On Hypoxiamentioning
confidence: 90%
“…Cysteine is also the precursor of sulfur-containing molecules such as taurine and lanthionine, which have cytoprotective functions. In addition to SP1, expression of CSE can also be regulated by the transcription factor, activating transcription factor 4 (ATF4) under conditions of stress (18,19).…”
mentioning
confidence: 99%